Is it possible to measure medical ethics learning? - Sogi, Cecilia (2005)
Objectives: 1) To assess the effectiveness of a medical ethics course; 2) to explore the factors that influence in moral reasoning; 3) to explore the perception of the most frequent ethical problems in clinics. Materials and Methods: Thirtyone general hospital first year medical residents participated in the study. A randomized pre test/post test crossover design was used with two groups, A and B. A questionnaire with two sections was administered: 1) close ended questions about personal data, factors that influence ethical decision and the most frequent ethical problems perceived in clinics; 2) open ended questions to vignettes. Results: Sixty-two per cent of all first year medical residents participated in the study. Mean age of the group was 29,6 (DE 3,90). Both A and B groups were similar in proportion of gender and age. Following the course respondents used less directive tone and more moral justification, and the use of values/principles ranking emerged. Personal values and beliefs, as well as family and general clinical experience were perceived as the most influential factors in ethical decisions. Medical error was perceived as the most frequent moral problem in clinics. Conclusion: The course had a positive effect, evidenced by the participants ability to use knowledge in case analysis.